Effectiveness, toxicity and impact on quality of life of high-dose-rate brachytherapy delivered in two fractions as monotherapy in patients with prostate cancer - Johan Staby Olsén; Antonis Valachis; Bengt Johansson (Clinical and Translational Radiation Oncology)
Purpose: The aim of this retrospective, single-center cohort study was to evaluate the effectiveness and safety of two-fraction high-dose-rate brachytherapy (HDR-BT) as monotherapy in a consecutive cohort of prostate cancer patients. Methods: We included consecutive patients who received 28 Gy HDR-BT in two fractions (14 Gy × 2) as monotherapy during 2005 to 2021 at our institution. Eligible patients were derived from an institutional database consisting of prospectively collected data. Primary endpoint was biochemical recurrence (BCR) and secondary endpoints included toxicity (assessed through both healthcare provider and patient-reported outcomes) and quality-of-life (QoL) assessment. Results: In total, 175 patients with prostate cancer (94 % classified as low- or intermediate-risk) were treated with HDR-BT during the study period with a median age of 68 years (range: 51–80), and a median follow-up of 60 months (range: 0–174). The estimated five-year cumulative BCR rate was 3.0 % (95 % Confidence Interval (CI): 0 %–13.3 %) for low-risk patients and 9.6 % (95 % CI: 4.7 %–16.7 %) for intermediate-risk patients. PSA exceeding 10 ng/mL at diagnosis was a significant risk factor for BCR (Odds Ratio (OR) = 3.29, 95 % CI: 1.01–10.67) whereas PSA of ≤0.1 ng/ml as nadir was a significant positive prognostic factor, associated with lower risk of BCR (OR = 0.11, 95 % CI: 0.03–0.33). At 12 months, 22 % of the patients had grade 2 and 3 % grade 3 urinary toxicity whereas 2 % of patients had grade 2 and none grade 3 bowel toxicity. At 12 months, 49 % of the patients with at least some erectile function before the treatment, had an impaired function. Conclusion: We found that two-fraction HDR-BT as monotherapy among patients with mainly low- and intermediate-risk prostate cancer appears to be safe in terms of biochemical recurrence, with a low proportion of severe urinary and bowel toxicity.